2019
DOI: 10.2478/kom-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Exposure tests of copper foils in a slurries of different bentonites

Abstract: The goal of the study was to compare corrosion performance of copper in different bentonite slurries. Copper coil samples were exposed in a slurries of bentonites BaM, Rokle, B75, G2M, Voltex, Sabenil. The test was carried out under anaerobic conditions in glovebox at laboratory temperature for duration of one to four months. Samples were evaluated by means of X-ray diffraction and mass loss. Liquid parts of slurries were analysed by ion chromatography and pH meter. The resistance of copper in all studied bent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…As shown in Figure 7, the size of the G phase with lower concentration of Cr than Cr-rich phase is about 40 nm which will reduce the stability and protective properties of passive film. While Park et al [22] and Stoulil and Bystriansky [19] observed the precipitation of Cr-rich phase induced the formation of a microscale Cr-depleted region which has a very fine size of about 10 nm and degrades the stability of passive film. The Cr-rich and G phases formed after the spinodal decomposition will decrease the stability of the passive film, and thus Cl − will destroy the weak region of the passive film.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 7, the size of the G phase with lower concentration of Cr than Cr-rich phase is about 40 nm which will reduce the stability and protective properties of passive film. While Park et al [22] and Stoulil and Bystriansky [19] observed the precipitation of Cr-rich phase induced the formation of a microscale Cr-depleted region which has a very fine size of about 10 nm and degrades the stability of passive film. The Cr-rich and G phases formed after the spinodal decomposition will decrease the stability of the passive film, and thus Cl − will destroy the weak region of the passive film.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, few concerns about the effect of thermal aging on the pitting corrosion of DSSs are performed. [3,[15][16][17][18][19][20][21] The Cr-rich, Fe-rich, and G phases formed during the spinodal decomposition are adjacent to each other. Comparing with the Cr-rich area, the Cr contents in the Ferich and G phases are lower than that in the Cr-rich phase.…”
Section: Introductionmentioning
confidence: 99%
“…15 The chemistry at the bentonite-UFC interface would also be profoundly affected by the exchange of cations into and out of the interlayer space and the ionization of surface -OH groups. 16 Corrosion of various test coupons in slurries of bentonite clay has been reported in previous work, 13,17,18 and those studies have shown that the bentonite clay can have a profound impact on corrosion even when hydraulic conductivity remains relatively high.…”
mentioning
confidence: 83%